Cystoid macular edema after cataract surgery in a patient with previous severe iritis following argon laser peripheral iridoplasty - Bagnis A (Dove Medical Press, 2011)
Alessandro Bagnis1, Sergio Claudio Saccà2, Michele Iester1, Carlo Enrico Traverso11Centro di Ricerca Clinica e Laboratorio per il Glaucoma e la Cornea, Clinica Oculistica Di NOG, University of Genova, 2Division of Ophthalmology, St. Martino Hospital, Genova, ItalyAbstract: This report describes a patient who had exaggerated responses to different inflammatory stimuli represented by laser and incisional surgery, respectively. These separate episodes should have a common link represented by a genetic predisposition to abnormal release of proinflammatory mediators within the eye. This 51-year old Hispanic woman showed a narrow iridocorneal angle with plateau iris configuration. Nd-YAG laser peripheral iridotomy was successfully performed to both eyes. No substantial changes in the iridotrabecular angle occurred despite patent iridotomies, thus confirming the diagnosis of plateau iris configuration. Argon laser iridoplasty was then performed to the right eye, while the left eye was scheduled for a later session. A severe inflammatory reaction within the anterior chamber developed after tapering of a one-week course of steroid therapy. Phacoemulsification of the lens was performed some months later when no signs of inflammation were detectable; no intraoperative complications occurred during surgery and an intraocular lens was placed. Cystoid macular edema developed four weeks after surgery despite no apparent risk factors, and resolved completely after anti-inflammatory medical therapy. Based on this case report, the unusual occurrence of severe iritis after laser treatment should be regarded as a risk factor for any other incisional or nonincisional procedures because it might indicate that the patient's ocular tissues are prone to release of abnormally elevated proinflammatory mediators. Although further studies are needed to confirm this predisposition, prophylactic adjunctive topical nonsteroidal anti-inflammatory drug administration after cataract surgery should be considered in such cases in order to prevent potentially sight-threatening conditions.Keywords: cystoid macular edema, inflammation, laser surgery, plateau iris configuration